Crushing and energy absorption characteristics of combined geometry shells at quasi-static and dynamic strain rates: Experimental and numerical study. (January 2015) - Tasdemirci, Alper; Sahin, Selim; Kara, Ali; Turan, Kivanc
Abstract: The quasi-static and dynamic crushing response and the energy absorption characteristics of combined geometry shells composed of a hemispherical cap and a cylindrical segment were investigated both experimentally and numerically. The inelastic deformation of the shells initiated with the inversion of the hemisphere cap and followed by the axisymmetric or diamond folding of the cylindrical segment depending on the loading rate and dimensions. The fracture of the thinner specimens in dynamic tests was ascribed to the rise of the flow stress to the fracture stress with increasing strain rate. The hemisphere cap absorbed more energy at dynamic rates than at quasi-static rates, while it exhibited lower strain rate and inertia sensitivities than the cylinder segment. For both the hemisphere cap and the cylinder segment, the inertial effect was shown to be more pronounced than strain rate effect at increasing impact velocities. Highlights: Static and dynamic crushing behaviors of combined geometry shells of hemisphere and cylinder were investigated. Numerical model was developed in order to investigate inertia and strain rates sensitivity of structure. The hemisphere cap absorbed more energy at dynamic rates than at quasi-static rates, while it exhibited lower strain rate and inertia sensitivities than the cylinder segment. Deformation sequence was determined both experimentally and numerically.